Lack of TAFI increases brain damage and microparticle generation after thrombolytic therapy in ischemic stroke. Issue 2 (August 2015) - Orbe, J.; Alexandru, N.; Roncal, C.; Belzunce, M.; Bibiot, P.; Rodriguez, J.A.; Meijers, J.C.M.; Georgescu, A.; Paramo, J.A.
Abstract Background Thrombin-activatable fibrinolysis inhibitor (TAFI) plays an important role in coagulation and fibrinolysis. Whereas TAFI deficiency may lead to a haemorrhagic tendency, data from TAFI knockout mice (TAFI −/−) are controversial and no differences have been reported in these animals after ischemic stroke. There are also no data regarding the role of circulating microparticles (MPs) in TAFI −/−. Objectives to examine the effect of tPA on the rate of intracranial haemorrhage (ICH) and on MPs generated in a model of ischemic stroke in TAFI −/− mice. Methods Thrombin was injected into the middle cerebral artery (MCA) to analyse the effect of tPA (10 mg/Kg) on the infarct size and haemorrhage in the absence of TAFI. Immunofluorescence for Fluoro-Jade C was performed on frozen brain slides to analyse neuronal degeneration after ischemia. MPs were isolated from mouse blood and their concentrations calculated by flow cytometry. Results Compared with saline, tPA significantly increased the infarct size in TAFI −/− mice (p < 0.05). Although plasma fibrinolytic activity (fibrin plate assay) was higher in these animals, no macroscopic or microscopic ICH was detected. A positive signal for apoptosis and degenerating neurons was observed in the infarct area, being significantly higher in tPA treated TAFI −/− mice (p < 0.05). Interestingly, higher numbers of MPs were found in TAFI −/− plasma as compared to wild type, after stroke (p < 0.05). Conclusions TAFI deficiency results in increased brain damage in a model of thrombolysis after ischemic stroke, which was not associated with bleeding but with neuronal degeneration and MP production.